Indoor residual spraying for malaria control in sub-Saharan Africa 1997 to 2017: an adjusted retrospective analysis - Tangena, JAA; Hendriks, CMJ; Devine, M; Tammaro, M; Trett, AE; Williams, I; DePina, AJ; Sisay, A; Herizo, R; Kafy, HT; Chizema, E; Were, A; et al. (BioMed Central, 2020)
Background: Indoor residual spraying (IRS) is a key tool for controlling and eliminating malaria by targeting vectors.To support the development of efective intervention strategies it is important to understand the impact of vector control tools on malaria incidence and on the spread of insecticide resistance. In 2006, the World Health Organization (WHO) stated that countries should report on coverage and impact of IRS, yet IRS coverage data are still sparse and unspecifc. Here, the subnational coverage of IRS across sub-Saharan Africa for the four main insecticide classes from 1997 to 2017 were estimated.